Low Blood Sugar: A Doctor's Guide to Its Effective Control - Hurdle J. F. (New York Parker Publishing Company, 1969)
The purpose of this pamphlet is to promote intelligent cooperation of patients with physicians. Patients will be able to notice and describe possible low blood sugar conditions and thus help their physicians in the correct diagnosis. They understand the meaning of restrictions before and during the glucose tolerance test and the purpose of other examinations. They will intelligently adhere to the prescribed diet because they understand the undesirable effect of the forbidden food items. Physicians save time in explaining their procedure by advising patients to read this pamphlet. They need to answer individual questions only. This time saving has an advantage to the patients; also, because it makes their visits shorter and less expensive At home they can study the instructions at leisure and will not forget them, because they have them in writing. -Hbci.com
.
Keywords: 61